Achievement Motivation And Emotional Intelligence As Predictors Of Mathematical Resilience Among Secondary School Students - Joy, Ugwu Chinelo; Obiagaeri, Ekechukwu Rosemary (Advances in Social Sciences Research Journal, 2019)
This study investigated achievement motivation and emotional intelligence as predictors of Mathematical resilience among senior secondary school students in Rivers Nigeria. Two research questions were answered and two hypotheses were tested at 0.05 alpha level. The population of the study comprised all 24,727 senior secondary school (SS2) students in the 247 public secondary schools in Rivers State. Sample size of 1690 was obtained using 20% of the population in simple random sampling technique. Three self-designed non-cognitive instruments titled Achievement Motivation Scale” (AMS), “Emotional Intelligence Scale” (EIS) and “Mathematical Resilience Scale” (MRS) were used for data collection. The AMS contained 14 items; EIS contained 17 items while MRS contained 20 items respectively. Face and content validities were carried out by the researchers along with three other experts in test, measurement and evaluation. The Cronbach reliability coefficient of 0.75, 0.72 and 0.77 were obtained for AMS, EIS and MRS respectively. Linear and multiple regressions were used to answer the research questions while t-test and ANOVA associated with linear and multiple regressions were used to test the null hypotheses. It was found among others that achievement motivation significantly predicted mathematical resilience. Emotional intelligence and achievement motivation jointly and significantly predicted mathematical resilience. It was recommended among others that guidance counselors should help students to reshape their minds from fixed to growth mindsets in order to become mathematical compliant as opposed to mathematical anxious.